Moving bed temperature swing adsorption processes for post-combustion CO2 capture - Meghani, Bishan (2015)
Due to high regeneration energy demands for amine absorption processes for post-combustion CO2 capture, alternative technologies such as adsorption processes using solid adsorbents have been considered. Other practical issues such as corrosion of equipment and loss of solvent can be avoided with adsorption processes. Fixed bed adsorption processes, in which CO2 adsorption and adsorbent regeneration are performed successively in a vessel packed with adsorbent, are the most common adsorption processes. However, in fixed bed temperature swing adsorption (TSA) processes, large columns and long heating and cooling times would be needed. Fixed bed pressure swing adsorption (PSA) processes use electrical energy, which is more expensive than thermal energy in a power plant. Therefore, the feasibility of moving bed adsorption processes including fluidised-bed, co-current and counter-current systems is investigated. In these systems, the adsorbent continuously circulates from a CO2 adsorber to a regenerator. The adsorbents considered are a supported amine adsorbent, activated carbon and zeolite 13X.